Rethinking development in South Asia issues, perspectives and practices - Ahamed, Farid Uddin; Islam, Mohammed Saiful; Nasrullah, Amir Mohammad (Cambridge Scholars Publishing, 2022)
This book challenges the way development has been conceptualized and practiced in the South Asian context and argues for its deconstruction in a way that would allow freedom, choice, and the greater well-being of the local people. Far from taking development for granted as growth and advancement, this book unveils how it can also be a destructive force in local socio-cultural and environmental contexts. By critically examining conventional development practices as hegemonic, devastating, and failing, this book highlights how rethinking development could be seen as "praxis", a matter of practice, by incorporating people's interests, priorities, and expectations--back cover